2012
DOI: 10.1158/1078-0432.ccr-12-0563
|View full text |Cite
|
Sign up to set email alerts
|

Combined PI3K/mTOR and MEK Inhibition Provides Broad Antitumor Activity in Faithful Murine Cancer Models

Abstract: Purpose Anticancer drug development is inefficient, but genetically engineered murine models (GEMM) and orthotopic, syngeneic transplants (OST) of cancer may offer advantages to in vitro and xenograft systems. Experimental Design We assessed the activity of 16 treatment regimens in a RAS-driven, Ink4a/Arf-deficient melanoma GEMM. In addition, we tested a subset of treatment regimens in three breast cancer models representing distinct breast cancer subtypes: claudin-low (T11 OST), basal-like (C3-TAg GEMM), an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
122
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(124 citation statements)
references
References 46 publications
1
122
1
Order By: Relevance
“…In fact, in tumor treatment, it was said that there were limitations of monotherapy for inhibiting feedbackregulated pathways and suggested that combined treatment with mTOR and P3IK/MAPK inhibitors would show more anti-tumor activity in a wide range of human malignance. 42 In line with this idea, we hypothesized that if rapamycin was used for the treatment of fibrotic diseases, combined inhibition of PI3K and mTOR pathways may have additive anti-fibrotic effects. Further in vivo studies should be designed to determine whether these findings are value.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, in tumor treatment, it was said that there were limitations of monotherapy for inhibiting feedbackregulated pathways and suggested that combined treatment with mTOR and P3IK/MAPK inhibitors would show more anti-tumor activity in a wide range of human malignance. 42 In line with this idea, we hypothesized that if rapamycin was used for the treatment of fibrotic diseases, combined inhibition of PI3K and mTOR pathways may have additive anti-fibrotic effects. Further in vivo studies should be designed to determine whether these findings are value.…”
Section: Resultsmentioning
confidence: 99%
“…The MEK/ERK and the PI3K/mTOR cascade are prototypic survival pathways that have been implicated in tumorogenesis of NRAS mutant melanoma (9,21). Emerging preclinical evidence suggests that combined targeting of these two pathways with selective small-molecule inhibitors might be effective in treating malignancies with preexistent or acquired RAS mutations (22)(23)(24)(25). In this study, we demonstrate that MEKi combined with PI3K/mTOR 1,2 inhibition is able to synergistically reduce cell viability in vitro and decrease tumor size in vivo in a large panel of human NRAS mutant melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using the MMTV-c-neu mouse model (a mouse model for breast cancer generated by the overexpression of the rat ortholog of HER2 V659E ) have shown evidence of the antitumor activity of lapatinib ( 10,11 ).…”
Section: Research Brief Functional Analysis Of Her2 V659ementioning
confidence: 99%